Integration of Solar Thermal Systems in Existing District Heating Systems - Wintersheid, Carlo (My University, 2016)
Modern district heating networks are usually operated with a changing flow temperature to cover the heat load of the supply area, depending on the outside temperature. Due to the minimum temperature requirements of individual customers, district heating (DH) networks also need to operate during the summer months. During this time, the load on the system is relatively low. This requires combustion facilities to also operate on low load levels. These systems have a potential of improving the energy efficiency by utilizing other energy sources such as waste heat from industrial processes or solar thermal systems. The overall aim of the presented work is to provide a methodology for the integration of solar heat into district heating The feasibility to include solar thermal systems in existing DH networks will be analysed based on the state-of-the-art of solar district heating (SDH). The main focus will be on large DH systems that are mainly supplied by fossil combined heat and power (CHP) plants considering how such plants can be operated in the future. Results will display characteristic technical, economic and ecological key performance indicators of the transformed DH system.
Keywords: Building Futures; Energi; Hållbar utveckling; Samhällsbyggnadsteknik; Building Futures; Energy; Sustainable Development; Civil Engineering